2017
DOI: 10.3382/ps/pew269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysophospholipid supplementation to lower nutrient diets on growth performance, intestinal morphology, and blood metabolites in broiler chickens

Abstract: The purpose of this research was to investigate the effects of dietary lysophospholipid (LPL) supplementation on low-energy, crude protein, and selected amino acids on growth performance, intestinal morphology, blood metabolites, inflammatory response, and carcass traits in broiler chickens. A total of 300 one-day-old male chicks (Ross 308) were assigned to 5 treatments, with 6 replications of 10 birds each in a completely randomized design. The 5 treatments were: positive control (PC) without LPL supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 29 publications
16
68
2
Order By: Relevance
“…However, the data of the present study are not in agreement with those of Raju et al (2011) and Boontiam et al (2016), who observed an increase in pancreatic weight when birds were fed with exogenous emulsifier, and the increase in relative body weight, according to the authors, might be indicative of increased digestion and lipid absorption.…”
Section: Concomitantcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the data of the present study are not in agreement with those of Raju et al (2011) and Boontiam et al (2016), who observed an increase in pancreatic weight when birds were fed with exogenous emulsifier, and the increase in relative body weight, according to the authors, might be indicative of increased digestion and lipid absorption.…”
Section: Concomitantcontrasting
confidence: 99%
“…The results show that a decrease in energy levels during the growing cycle negatively affected weight gain and the feed conversion of broilers, possibly due to a lower CME. In the same way, Boontiam et al (2016), when evaluating two metabolisable energy programmes (mean: 2875, 3000, and 3050 and high: 3025, 3150, and 3200 Kcal kg -1 , for phases 1 to 7, 8 to 21, and 22 to 35 days, respectively) reported lower weight gain at the end of the growing cycle in birds fed diets containing the lowest levels of metabolisable energy. These results also suggest that modern broiler chickens are less efficient at regulating feed intake according to the metabolisable energy level with increasing age.…”
Section: Concomitantmentioning
confidence: 81%
“…Furthermore, supplementation of a rice-bran-derived lysolecithin increased fat digestibility and improved growth performance of broiler chickens (16) . The advantages of dietary supplementation with lysophospholipid for improving lowenergy and low-nitrogenous diets were also recently observed in a study by Boontiam et al (17) . Similarly, Siyal et al (18) confirmed an increased digestibility of energy due to soyabean lecithin utilisation in the broiler chicken diets, which could be an effective strategy to decrease dietary ME levels.…”
supporting
confidence: 60%
“…Previous studies showed different results due to the addition of emulsifier supplementation to animal diet. For example, Boontiam et al (17) reported that the VH, CD and VH:CD ratio in the broiler jejunum were improved as the result of supplementation with lysophospholipid (0•5, 1 and 1•5 g/kg); but with respect to the duodenal morphology, only CD was decreased by lysophospholipid. Alzawqari et al (19) also showed linear increases in VH, VSA and VH:CD ratio in the jejunum and ileum, but no morphological changes in the duodenum by feeding desiccated ox bile to broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, partial hydrolysis using lipase from R. oryzae was performed to cleave off the FA moiety bound at the sn-1 position of the squid crude PL. In recent years, the sn-1 and sn-2 positional isomers of LPC and the molecular species of PL has been analyzed by using 31 P NMR 27 . Further studies are necessary to confirm the ratio of sn-1 and sn-2 position isomers of LPC in the DHA-LPC rich oil.…”
Section: Discussionmentioning
confidence: 99%